Developing tactics for listening. - Richards, Jack C. (New York : Oxfort University Prees, 2010)
A classroom-proven, American English listening skills course for upper secondary, college and university students.
Listening - Pronunciation & Dictation - Conversation.
Incluye contents.
Keywords: English language -- Textbooks for foreign speakers; English language -- Study and teaching -- Foreign speakers; English language -- Sound recordings for foreign speakers; Listening -- Problems, exercises, etc; Listening; English language